2017
DOI: 10.1021/acs.orglett.7b02271
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Chondroitin Sulfate A Bearing Syndecan-1 Glycopeptide

Abstract: Syndecan-1 chondroitin sulfate glycopeptide was synthesized for the first time using the cassette approach. The sequence of glycosylation to form the octasaccharide serine cassette was critical. The glycopeptide was successfully assembled via a 2+ (3 + 3) glycosylation strategy followed by peptide chain elongation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…The stereochemistry of the new glycosidic bond was confirmed by 1 H NMR spectrometry ( J H1‴,2‴ = 8.4 Hz). This result further indicated that the failed glycosylation reactions in Schemes and were probably because of the low reactivity of trisaccharide 4 . It was worth noting that the glycosylation reaction of 16 with a 4- O -Fmoc derivative of diol 7 gave a pentasaccharide byproduct, which could be avoided by using donor 24 .…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The stereochemistry of the new glycosidic bond was confirmed by 1 H NMR spectrometry ( J H1‴,2‴ = 8.4 Hz). This result further indicated that the failed glycosylation reactions in Schemes and were probably because of the low reactivity of trisaccharide 4 . It was worth noting that the glycosylation reaction of 16 with a 4- O -Fmoc derivative of diol 7 gave a pentasaccharide byproduct, which could be avoided by using donor 24 .…”
Section: Resultsmentioning
confidence: 90%
“…This result further indicated that the failed glycosylation reactions in Schemes 4 and 5 were probably because of the low reactivity of trisaccharide 4. 21 It was worth noting that the glycosylation reaction of 16 with a 4-O-Fmoc derivative of diol 7 gave a pentasaccharide byproduct, which could be avoided by using donor 24. Subsequently, 26 was glycosylated with sialodisaccharide 6 under the promotion of NIS and TfOH to provide 27 (J H1⁗,2⁗ = 8.4 Hz) smoothly, which was eventually desilylated with 3HF•Et 3 N to furnish 14.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In turn, 3 can be generated using a cassette approach from glycosyl serine-glycine 4 building block followed by peptide chain elongation (Scheme 1). While previous synthesis utilized glycosyl serine as the cassette for peptide synthesis, 26,48 we found that the glycosylated serine was prone to base promoted glycan elimination (Fig. 2c) during coupling with peptides more than ve amino acids long.…”
Section: Synthetic Design Of Syndecan-4 Glycopeptidesmentioning
confidence: 81%
“…Our work originated from the efforts toward the synthesis of heparan sulfate/chondroitin sulfate proteoglycan glycopeptides, which contain a tetrasaccharide linker of glucuronic acid (GlcA)-β-1,3-galactose (Gal)-β-1,3-Gal-β-1,4-xylose (Xyl). To form this linkage region, we first synthesized the Gal-Gal disaccharide donor 3 bearing two levuniloyl (Lev) groups by the glycosylation of the bifunctional acceptor 2 with thiogalactosyl donor 1 followed by benzoylation (Scheme ).…”
mentioning
confidence: 92%